Recent Advances and Perspectives in Microfluidics‐Based Single‐Cell Biosensing Techniques. Issue 10 (13th September 2017) - He, Jiacheng; Brimmo, Ayoola T.; Qasaimeh, Mohammad A.; Chen, Pengyu; Chen, Weiqiang
Abstract: Single‐cell analyses of secretory proteins are essential to fully understand cellular functional heterogeneity and unravel the underlying mechanisms of intercellular signaling and interactions. Retrieving dynamic information of protein secretion at single‐cell resolution reflects the precise, real‐time functional states of individual cells in physiological processes. Such measurements remain very challenging in single‐cell analysis, which requires highly integrated systems capable of performing on‐chip single‐cell isolation and subsequent real‐time protein detection. Here, recent advances in microfluidics‐based single‐cell manipulation and emerging approaches for label‐free single‐cell biosensing are reviewed. The advantages and limitations of these technologies are summarized and challenges to establish the integrated microfluidic biosensing systems for real‐time single‐cell secretomics are discussed. Recent efforts on integrated platforms for on‐chip single‐cell protein assays are highlighted and some perspectives on future directions in this field are provided. Abstract : Single‐cell secretion analyses are important for understanding cellular phenotypes and functional heterogeneity. The integration of microfluidic single‐cell manipulation system with label‐free sensing techniques enables in situ, real‐time monitoring dynamic protein‐secretion profiling with high spatial and temporal resolution. Such integrated single‐cell analysis systems hold great promise for advancing disease diagnosis and therapeutic treatment for clinical applications.